Adherence to clinical practice guidelines for Management of epithelial precancerous conditions and lesions in the stomach in Europe - Fontes, Filipa; Kapteijn, Noa E. A.; Hassan, Cesare; Deane, Charlene; Cristiano, Margarida; Fernandes-Mendes, Henrique; Luzko, Irina; Čavlina Sevo, Maša; Kelly, Orlaith; Esposito, Gianluca; Holster, I Lisanne; van der Horst, Michiel P. J.; Kweldam, Charlotte F.; Voiosu, Andrei; Pinto, Ricardo Marcos; Almeida, Nuno; O'Morain, Colm; Moreira, Leticia; Bornschein, Jan; Spaander, Manon C.W.; Dinis-Ribeiro, Mário (Endoscopy, 2025)
The first international guideline for managing preneoplastic conditions of the stomach (MAPS I) was published in 2012, followed by an update (MAPS II) in 2019. As adherence to these guidelines remains uncertain, we evaluated adherence by comparing the management of preneoplastic gastric conditions before and after the introduction of MAPS I and II in selected European centers.Patient data were retrieved from nine endoscopy units in seven European countries during three periods: pre-MAPS I (2010/2011), post-MAPS I (2017/2018), and post-MAPS II (2022/2023). Screening and dyspepsia-related endoscopies were included. Data on endoscopies, histopathology, Helicobacter pylori treatment, and surveillance were collected using a standardized form. Adherence to nine MAPS recommendations was assessed, with improvement defined as a ≥10-percentage point increase in guideline-concordant management.A total of 2426 patients were included. Over the years, most centers (57%) improved in seven of the nine recommendations. Virtual chromoendoscopy use improved in six centers, with four reporting its use in >50% of cases. All centers improved in performing biopsies from the antrum and corpus, five conducted random biopsies in nearly all patients, and four performed these plus a biopsy from the incisura in >90% of cases. Endoscopic scores for patient stratification were rarely used, although five centers improved in histological scoring or intestinal metaplasia subtyping. H. pylori treatment recommendations remained high (71%–100%), and endoscopic surveillance adherence improved in 4/7 centers.Adherence to MAPS guidelines improved in most centers; however, gaps in virtual chromoendoscopy, targeted biopsies, and endoscopic/histopathological scoring remain, potentially affecting surveillance recommendations. This underscores the need for a more tailored approach to enhance implementation.